Needs Analysis of English for Specific Purposes (ESP) for Office Management Automation of VHS Students - Syanindita Nuruliza, - (2022)
In Indonesia, English is a part of curriculum in the Senior High School/ Vocational High School. Furthermore, it has little difference between high school (SMA) and vocational high school (VHS/SMK). English learned at elementary to senior high schools is a general English while in vocational high school it is called ESP (English for Specific Purposes). This paper reports on the result of a study aiming at needs analysis of English for Specific Purposes (ESP) for OTKP (Otomasi dan tata kelola perkantoran/office Management automation) students. This present study employed a qualitative case study method with two data collection techniques, including: questionnaires, and interviews. The data were collected from 81 students and one English teacher. Furthermore, the researcher chooses seven respondents to be interviewed for further investigation. The results showed that all of OTKP (Otomasi dan tata kelola perkantoran/office management automation) students agreed that English for Specific Purposes (ESP) is very important for their major but had low interest towards English. However, the teacher admitted that she has limited knowledge, but she would like to improve her knowledge of technical terms in OTKP (Otomasi dan tata kelola perkantoran/office management automation)